Inhalation of molecular hydrogen prevents ischemia-reperfusion liver damage during major liver resection - Malý, Ondřej; Zajak, Ján; Hyšpler, Radomír; Turek, Zdeněk; Astapenko, David; Jun, Daniel; Váňová, Nela; Kohout, Aleš; Radochová, Věra; Kotek, Jiří; Páral, Jiří (Annals of translational medicine, 2019)
BACKGROUND: Liver resection is a surgical procedure associated with a high risk of hepatic failure that can be fatal. One of the key mechanisms involves ischemia-reperfusion damage. Building on the well-known positive effects of hydrogen at mitigating this damage, the goal of this work was to demonstrate the antioxidant, anti-inflammatory, and anti-apoptotic effects of inhaled hydrogen in domestic pigs during major liver resection. METHODS: The study used a total of 12 domestic pigs, 6 animals underwent resection with inhaled hydrogen during general anesthesia, and 6 animals underwent the same procedure using conventional, unsupplemented, general anesthesia. Intraoperative preparation of the left branch of the hepatic portal vein and the left hepatic artery was performed, and a tourniquet was applied. Warm ischemia was induced for 120 minutes and then followed by liver reperfusion for another 120 minutes. Samples from the ischemic and non-ischemic halves of the liver were then removed for histological and biochemical examinations. RESULTS: An evaluation of histological changes was based on a numerical expression of damage based on the Suzuki score. Liver samples in the group with inhaled hydrogen showed a statistically significant reduction in histological changes compared to the control group. Biochemical test scores showed no statistically significant difference in hepatic transaminases, alkaline phosphatase (ALP), lactate dehydrogenase (LD), and lactate. However, a surprising result was a statistically significant difference in gamma-glutamyl-transferase (GMT). Marker levels of oxidative damage varied noticeably in plasma samples. CONCLUSIONS: In this experimental study, we showed that inhaled hydrogen during major liver resection unquestionably reduced the level of oxidative stress associated with ischemia-reperfusion damage. We confirmed this phenomenon both histologically and by direct measurement of oxidative stress in the organism.
Keywords: reactive oxygen species (ROS); oxidative stress; oxidative damage markers; Ischemia-reperfusion injury; hepatic impairment